Shining a Light on the “T” in STEM - Nolting, Sarah; Wilcox, Jesse; Moore-Dilworth, Naryah; Grenko, Mackenzie (Science and children, 2021)
Even though children interact with the natural and designed worlds daily, they don't often think and act like scientists and engineers. The Next Generation Science Standards call for engaging students in practices that scientists and engineers use, but it's also important to explicitly teach thinking approaches that scientists and engineers use. One way to help children think and act like scientists and engineers is to engage them with computational thinking (CT). CT is "a problem-solving methodology that can be automated and transferred and applied across subjects." This can involve breaking problems into smaller pieces, recognizing patterns, and making basic algorithms to solve problems.